Distribution and chemotaxonomic significance of phenolic compounds in Spermacoce verticillata (L.) G. Mey - Iasmim C. Lima (Journal of Pharmacy & Pharmacognosy Research, 2014)
Context: Spermacoce verticillata, known as “poaia and vassourinha de botão”, is a species widely used in Brazilian traditional medicine as anti-inflammatory, antipyretic and analgesic. It is a native species, small, upright perennial, and broadly distributed throughout Brazil. Until now, few chemical studies have focused on the phenolic composition of this species. Aims: Evaluate the phytochemical profile of phenolic compounds from Spermacoce verticillata and search new compounds that have chemotaxonomic significance. Methods: Leaves of S. verticillata were extracted using distilled water. The extract (SVL) was purified by several chromatography processes. Extract and compounds were analyzed by HPLC-DAD and NMR. Results: Phytochemical analysis led to identification, for the first time, of three compounds (1-3) for the specie. Chlorogenic acid (1) was identified by HPLC-DAD compared with reported in the literature. Quercetin-3-O-rutinoside (rutin) (2) and kaempferol-3-O-rutinoside (3) were isolated from butanolic fraction and identified by spectroscopic analysis comparison with data reported in the literature. The flavonoid rutin is the major compound in SVL followed by kaempferol-3-O-rutinoside and chlorogenic acid. Conclusions: This is the first report for these compounds (1-3) in S. verticillata. The presence of these three new compounds indicates chemical markers of the species for this genus and family. This information is extremely important because increases the resources for chemotaxonomic classification of these species.